2020
DOI: 10.1080/16742834.2020.1814675
|View full text |Cite
|
Sign up to set email alerts
|

CAS FGOALS-f3-H and CAS FGOALS-f3-L outputs for the high-resolution model intercomparison project simulation of CMIP6

Abstract: The High Resolution Model Intercomparison Project (HighResMIP) is a unique model intercomparison project in phase 6 of the Coupled Model Intercomparison Project (CMIP6), which is focused on the impact of horizontal resolutions. The outputs of the high-and low-resolution versions of CAS FGOALS-f3-H and CAS FGOALS-f3-L for the experiments of the HighResMIP simulations in CMIP6 are described in this paper. The models and their configurations, experimental settings, and postprocessing methods are all introduced. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The global dust simulations are conducted using the SPRINTARS (Spectral Radiation Transport Model for Aerosol Species) aerosol model (Takemura et al, 2005(Takemura et al, , 2009, which is coupled online with the CAS-FGOALS-f3 (the Chinese Academy of Sciences Flexible Global Ocean-Atmosphere-Land System) GCM (Bao et al, 2013(Bao et al, , 2020Wang et al, 2020;Zhao et al, 2022). The size distribution of dust particles in the SPRINTARS model is categorized into 10 bins, ranging from 0.2 to 20 μm in diameter (Takemura et al, 2000).…”
Section: Cas-fgoals-sprintarsmentioning
confidence: 99%
“…The global dust simulations are conducted using the SPRINTARS (Spectral Radiation Transport Model for Aerosol Species) aerosol model (Takemura et al, 2005(Takemura et al, , 2009, which is coupled online with the CAS-FGOALS-f3 (the Chinese Academy of Sciences Flexible Global Ocean-Atmosphere-Land System) GCM (Bao et al, 2013(Bao et al, , 2020Wang et al, 2020;Zhao et al, 2022). The size distribution of dust particles in the SPRINTARS model is categorized into 10 bins, ranging from 0.2 to 20 μm in diameter (Takemura et al, 2000).…”
Section: Cas-fgoals-sprintarsmentioning
confidence: 99%
“…This enhancement of the atmospheric component results in improved computational efficiency and accuracy. Besides, the key parameterization in FAMIL2 is a Resolved Convection Precipitation scheme (RCP), which is independently developed to calculate the microphysics processes in the convective precipitation for both deep and shallow convection (Bao and Li, 2020). Due to the rapid phase changes occurring within the convective cloud, a sub-time step of 150 seconds is employed for the calculation of microphysical processes within a physical timestep of 30 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations involving the finer resolution model of HighResMIP may shed more lights on climate change. Recently, related works based on HighResMIP models have reported that the enhancement of horizontal resolution can significantly improve the performance of models for the diurnal variation of tropical cyclones and the resulting precipitation (Bao et al, 2020;Zhang et al, 2021). However, there is a lack of studies on evaluation of precipitation simulation over the complex terrain by using CMIP6 HighResMIP models.…”
Section: Introductionmentioning
confidence: 99%